The Amalgamation of Chinese Higher Education Institutions - David Y. Chen (Arizona State University, 2002)
The 1990s witnessed revolutionary change in China's higher education system, particularly through radical mergers. The reform process and its background are detailed here, with a case study focusing on Zhejiang University. After nearly 15 years of painstaking effort, the reform goals for the higher education system have been met, and a decentralized, two-tiered administrative system has been installed. However, the most hotly debated reform has been the amalgamation of universities. The need to optimize China's system of higher education has a background dating back about 50 years, when the first reordering of higher education took place. The reordering and its results are described, and the causes and after effects of this reform are detailed.